Meaningful and Meaningless Solutions for Cooperative N-person Games - Pekec, Aleksandar (BRICS Report Series, 1996)
Game values often represent data that can be measured in more than one acceptable way (e.g. monetary amounts). We point out that in such a case a statement about cooperative n-person game model might be "meaningless" in the sense that its truth or falsity depends on the choice of an acceptable way to measure game values. In particular we analyze statements about solution concepts such as the core, stable sets, the nucleolus, the Shapley value (and its generalizations). Keywords: Cooperative n-person Games, Measurement, Sensitivity Analysis.